Mortality and Clinical Predictors After Percutaneous Mitral Valve Repair for Secondary Mitral Regurgitation: A Systematic Review and Meta-Regression Analysis - Shi, Wence; Zhang, Wenchang; Zhang, Da; Ye, Guojie; Ding, Chunhua (Frontiers in Cardiovascular Medicine, 2022)
Background Percutaneous mitral valve repair (PMVR) provides an available choice for patients suffering from secondary mitral regurgitation (SMR), especially those whose symptoms persist after optimal, conventional, heart-failure therapy. However, conflicting results from clinical trials have created a problem in identifying patients who will benefit the most from PMVR. Objective To pool mortality data and assess clinical predictors after PMVR among patients with SMR. To this end, subgroup and meta-regression analyses were additionally performed. Methods We searched PubMed, EMBASE, and Cochrane databases, and 13 studies were finally included for meta-analysis. Estimated mortality and 95% confidence intervals (CIs) were obtained using a random-effects proportional meta-analysis. We also carried out a meta-regression analysis to clarify the potential influence of important covariates on mortality. Results A total of 1,259 patients with SMR who had undergone PMVR were enrolled in our meta-analysis. The long-term estimated pooled mortality of PMVR was 19.3% (95% CI: 13.6–25.1). Meta-regression analysis showed that mortality was directly proportional to cardiac resynchronization therapy (CRT) (β = 0.009; 95% CI: 0.002–0.016; p = 0.009), an effective regurgitant orifice (ERO) (β = 0.009; 95% CI: 0.000–0.018; p = 0.047), and a mineralocorticoid receptor antagonist (MRA) use (β = −0.015; 95% CI: −0.023–−0.006; p < 0.001). Subgroup analysis indicated that patients with preexisting AF (β = −0.002; 95% CI: −0.005– −0.000; p = 0.018) were associated with decreased mortality if they received a mitral annuloplasty device. Among the edge-to-edge repair device group, a higher left ventricular (LV) ejection fraction, or lower LV end-systolic diameter, LV end-systolic volume, and LV end-diastolic volume were proportional to lower mortality. Conclusion and Relevance The pooled mortality of PMVR was 19.3% (95% CI: 13.6–25.1). Further meta-regression indicated that AF was associated with a better outcome in conjunction with the use of a mitral annuloplasty device, while better LV functioning predicted a better outcome after the implantation of an edge-to-edge repair device.